A study of Chinese Adults’ motivation to learn a third or more languages - Li, J (2022)
The level and nuances of motivation when learning third or more languages has not yet been widely researchd despite China having a large population of English language learners. This paper constitutes a quantitative study, involving a questionnaires designed to validate the scale of the third language (L3) motivation, and to compare the motivation of male and female adults (the first language (L1) is Chinese) when learning three or more languages. The data were collected and analysed using the R software online via a questionnaires (N = 398). Exploratory factor analysis, confirmatory factor analysis, and full structural equation modelling were undertaken to answer the research questions raised, as well as analyses of variance (ANOVA) with likelihood ratio tests, chi-squared different tests, Shapiro-Wilk test and Wilcoxon test with a bonferroni correction.